أولويات الأساتذة الجامعيين الجزائريين على الفايسبوك؛ دراسة تحليلية لمنشوراتهم الإلكترونية - عيساني سعاد; هدار خالد (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2021)
تحاول هذه الدراسة التعرف على أولويات الأساتذة الجامعيين الجزائريين من خلال منشوراتهم على الفايسبوك، انطلاقا من إشكال أساس: ما هي أجندة الأساتذة الجامعيين الجزائريين من خلال منشوراتهم على الفايسبوك؟، وقد قمنا بتحليل منشورات الأساتذة الجامعيين عينة الدراسة على الفايسبوك باستخدام أداة تحليل المحتوى، وجاء اختيارنا للأساتذة عينة الدراسة بطريقة قصدية بناء على الأكثر نشاطا على هذه الشبكة، وقد توصلنا بعد الدراسة الميدانية إلى أن أولويات الأساتذة الجامعيين تختلف على الفايسبوك عن أولويات وسائل الإعلام الجماهيرية، حيث أن الأساتذة الجامعيين يركزون في منشوراتهم على مواكبة التطورات والمستجدات اليومية في حياتهم العلمية والعملية بالدرجة الأولى، فقد تركزت أولوياتهم على الجانب العلمي أولا ثم الجانب الاجتماعي ليليه الجانب السياسي والديني. Abstract: This study attempts to identify the priorities of Algerian university teachers through their Facebook’s posts, based on a basic problem: What is the agenda of Algerian university teachers through their Facebook posts? We analyzed the posts of university teachers, the study sample on Facebook, using the content analysis tool, and our selection of teachers of the study sample was intentionally based on the most active on this network. After the field study, we concluded that the priorities of university professors differ on Facebook from those of the mass media as university teachers focus in their publications on keeping up with the daily developments and advancement in their scientific and practical lives in the first place. Actually, their priorities focused first on the scientific side, then the social aspect, followed by the political and religious side.